Effect of Slice Moisture on the Quality of Potato Chips - Karki, D. B.; Maskey, S. (Tribhuvan University Journal, 2011)
Available with full text. Key words: Potato chips; Slice; Sulphur dioxide; NaCI Tribhuvan University Journal Vol XXIII, No. 1, 2001 Page: 51-54 Uploaded date: 21 April, 2011